STUDY OF BALAGHAH: The Context of Understanding Al-Qashar in Surah Al-Kafirun Verse 6 in Relation to Various Attitudes of Religious Tolerance in Indonesian Society. - Mitra, Rohma; Rahma, Nazwa Awallul (Yayasan Haiah Nusratul Islam, Indonesia, 2025)
Indonesia is a country with religious diversity, so the issue of religious tolerance is very important to maintain social harmony. One of the verses of the Qur'an that is often used as a basis for understanding tolerance is Surah Al-Kafirun verse 6,